Aspectos das mudanças sociais na educação: alunos diante de coordenadas inseguras - Machi, Gilzane Santos (2009)
The following thesis has attempted to map and evaluate contributions and limitations of current social changes and post-modernity thinking in relation to students, instructors and school. The aim of this thesis is to analyze how the student views the school, and its instructors in a fast paced society that is constantly transforming. It is now common to find intellectuals from many fields of study questioning aspects of modern society. It can be said that the following thesis is joining this recent critical evaluation of modern society. Specifically, this thesis will evaluate one of the most important institutions of this society, education. The goal of this thesis is to reflect on how the school, contents, methodologies, and interpersonal relationships act when confronted with post modernism. The objective of this study is also to consider the interconnection of educational theory and practice in the light of contemporary social changes; and to analyze the school, its contents, methodologies, and interpersonal relationships in order to understand where the paradigmatic aspects of post-modernity society can interfere with the student s behavior, and how the ill-behavior can be related to the uneducated instructors confronted with post-modern thought. The primary case study was a secondary public school which was analyzed in multiple dimensions; in actions, practices, and speeches of different members of the school with a focus on how current students view the instructors. Further support is supplied by a theoretic chart composed of studies and reflections of different authors that discuss the current educational changes facing our society.